Effect of Supply Chain Disruptions and Inflation on the Ohio Construction Industry in 2023 - Atalah, Alan; Al-Azanki, Walid (Eximia, 2025)
In 2023, the US (and the rest of the world) encountered supply chain disruptions due to the COVID 19 recovery, Russia’s invasion of Ukraine, and the expiration of government subsidies during 2020 and 2021. The construction of many multibillion dollars facilities and infrastructure projects created additional demand. In 2020-21, COVID 19 disturbed the balance of the labor market; many businesses laid off a portion of their workforce; consequently, many workers retired, changed professions, moved, etc. creating a shortage of workforce. In addition, high inflation rates close to 10% in the US (and higher in many parts of the world) was the natural result of this supply chain disturbance and labor shortage. The authors hypothesize that these economic forces and challenges affected the construction industry which is a significant part of the US economy. This research attempts to examine this hypothesis through a survey designed to capture the opinions of construction professional. The research also tries to: • Determine the impact of supply chain disturbance, labor shortage, and inflation on the construction industry. • Figure out how the construction industry reacted to these challenges The findings of this research would give us a snapshot at the state of the construction industry, and it can help the industry deal with the similar challenges in the future.